Synthesis and characterization of organic-inorganic membranes containing sulphogroups - Yevchuk, Iryna; Demchyna, Oksana; Kochubey, Viktoriya; Romaniuk, Hanna; Koval, Zenoviya (Lviv Polytechnic Publishing House, 2013)
Organic-inorganic materials have been synthesized by photoinitiated copolymerization of monomers: acrylonitrile, acrylamide and 3-sulphopropyl acrylate potassium salt in the presence of sol-gel systems based on tetraethoxysilane. Thermal stability, water uptake and ion-exchange capacity of obtained materials have been determined. Undertaken studies may be used for development of protonconductive membrane for fuel cells. Синтезовано органо-неорганічні сульфовмісні мембрани методом фотоініційованої кополімеризації мономерів акрилонітрилу, акриламіду і сульфопропілакрилату в присутності золь-гель систем на основі тетраетоксисилану. Визначено термічну стабільність,водопоглинання і йонообмінну ємність одержаних матеріалів. Проведені дослідження можуть бути використані при розробленні протонпровідних мембран для паливних елементів.
Синтез і характеристика органо-неорганічних сульфовмісних мембран
Keywords: organic-inorganic composite; hydrogel; polyelectrolyte; protonconductive membrane; sol-gel method; photoinitiated copolymerization; органо-неорганічний композит; протон-провідна мембрана; йонообмінна ємність; золь-гель метод; фотоініційована кополімеризація